An Empirical Study on the Factors Affecting Consumer Behavior in the Fast-Food Industry - Irshad Ahmad Reshi; Shabir Ahmad Dar; Shaikh Sobiya Ansar (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
Abstract This empirical study investigates the factors that affect consumer behavior in the fast-food industry. The research examines the role of various factors, including quality of food, price, convenience, location, and brand image, in determining the behavior of consumers when purchasing fast food. The study uses a quantitative research approach to gather data from a sample of 500 respondents using an online survey. The results suggest that quality of food and price are the most significant factors influencing consumer behavior in the fast-food industry. However, convenience, location, and brand image also play a significant role in determining consumer behavior.